My Culture, My Color, My Self : Heritage, Resilience, and Community in the Lives of Young Adults - Jenkins, Toby S. (Toby Susann), 1975- (Book collections on Project MUSE., 2013)
Examines how young adults discover their cultures through education, art, spirituality, and personal survival strategies. Provides an analysis of why minority youth's cultural backgrounds should be acknowledged by institutions of higher education in order for the students to excel.